2010
DOI: 10.4314/ijbcs.v3i5.51053
|View full text |Cite
|
Sign up to set email alerts
|

The purification and some properties of rhodanese from tortoise (Kinixys erosa, Schweigger) liver

Abstract: Rhodanese (cyanide: thiosulphate sulphur transferase; EC.2.8.1.1) was isolated from cytosolic fraction of tortoise liver using ammonium sulphate fractionation, ion exchange chromatography and gel filtration from the liver of tortoise. The enzyme had a specific activity of 14.43 RU per milligram of protein.The K m values for KCN and Na 2 S 2 O 3 were 16 mM and 30.0 mM respectively. The native and subunit molecular weight of the enzyme was found to be 33,000 and 35,000 dalton respectively. The optimum pH and tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…Agboola and Okonji (2004) reported the inhibition of fruit bat rhodanese by Ba 2+ and Zn 2+ . This is also supported by the report of Aladesanmi et al (2009) . Inhibition by salts and certain monovalent anions may be due in part, to an increase in the ionic strength of the medium (Mintel and Westley, 1966).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Agboola and Okonji (2004) reported the inhibition of fruit bat rhodanese by Ba 2+ and Zn 2+ . This is also supported by the report of Aladesanmi et al (2009) . Inhibition by salts and certain monovalent anions may be due in part, to an increase in the ionic strength of the medium (Mintel and Westley, 1966).…”
Section: Resultssupporting
confidence: 84%
“…A pH range of 8.0 to 11.5 has been reported in various works (Chew and Boey, 1972;Lee et al, 1995;Agboola and Okonji, 2004;Okonji et al, 2010). The pH optimum of 8.5 was obtained for rhodanese from the liver of land tortoise (Aladesanmi et al, 2009). It has also been reported that at low pH (4 to 6) rhodanese is stabilized against inactivation (Kurban and Horowitz, 1991).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Rhodanese has been reported in many organisms from bacteria to animals (Agboola and okonji, 2004;Aladesanmi et al, 2009;Itakorode et al, 2019). In this study, we report the presence of rhodanese, a cyanide detoxifying enzyme in the kidney of grasscutter (T. swinderianus).…”
Section: Discussionmentioning
confidence: 99%